Pemberdayaan Kader Pendamping Keluarga dalam Pencegahan Anemia Remaja melalui Edukasi dan Pendampingan di Kelurahan Banjarsari, Kulon Progo - Munica Rita Hernayanti; Dwiana Estiwidani; Maranata Maranata (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
Anemia among adolescent girls remains a significant public health problem with long-term implications for human resource quality. Limited knowledge and suboptimal family involvement in anemia prevention pose major challenges at the community level, including in Banjarsari Village, Kalibawang, Kulon Progo. This community service program aimed to enhance the capacity of health cadres through the establishment of family companion cadres for the prevention of anemia among adolescents. This program employed a community empowerment approach using a participatory model that integrated education, training, and cadre mentoring. The participants consisted of 32 health cadres selected based on their active involvement in community health activities. The intervention included educational sessions using leaflets and an audiovisual medium (CAMAR video), as well as strengthening the role of cadres in family-based assistance. Program evaluation was conducted using a pre-test and post-test design to assess changes in knowledge. The results showed full participation of all cadres, with an increase in the mean knowledge score from 65.05 to 76.7. Participants demonstrated active engagement during the sessions and an improved understanding of their role in educating and supporting families in adolescent anemia prevention. This program indicates that a cadre-based empowerment approach is effective in improving knowledge and strengthening the role of cadres as agents of change within the community. The findings suggest increased potential for cadres to support promotive and preventive efforts in family-based anemia prevention. In conclusion, the establishment of family companion cadres represents a relevant and practical strategy for preventing anemia among adolescents. Further efforts are needed to ensure program sustainability through continuous mentoring and integration with local health services.